Rationale and Problems for Use of Coptis and Berberine in Cancer Chemoprevention - Liu, MD, PhD, Jing; He, PhD, Zhengwei (North American Journal of Medicine and Science, 2008)
Coptis (Huang Lian) is a very popular therapeutic herb in China. The pharmacological name of coptis is rhizoma coptidis and the botanical name is coptis chinesis franch. Coptis grows in many areas around the globe. There are about 15 major species of coptis in China, including C. chinesis, C. deltoidea, C. orneiensis, C. teetoides and C. quinquesecta. Coptis chinensis, or duan e huang lian in Chinese, has been widely used in traditional Chinese medicine. Coptis aspleniifolia (spleenwort-leaf goldthread) and coptis occidentalis (Idaho Goldthread) are popular herbs native to North America.